Pengaruh Komposisi Kulit Durian Dan Kulit Pisang Terhadap Nilai Kalor Sebagai Briket Bioarang - Erlinda Ningsih; Yustia Wulandari Mirzayanti2; Mochamad Agil Yogi Parama (Seminar Nasional Teknik Kimia Kejuangan, 2017)
The wastes of durian and bananas peel are used as bio charcoal briquettes whis is the alternative of waste agriculture treatment. This technology can improve the economic value and be environmentally friendly. The aim of this study is to determine the particle size of mixture composition between bio charcoal briquettes, banana peel, and durian peel towards the calory of briquettes. The pyrolysis takes place on the temperature 3000C for 2.5 hours. Proximate analysis consist of water level test, the percentage of bio charcoal dust, and the calory of briquettes test. The result of this study can be concluded that the higher 5348.50 kkal/kg, was obtained by 80:10 of durian and banana peel ratio using 100 mesh of particle size. This results indicate that the higher composition of durian peel produces high the calory of briquettes and the lower particle size causes high the calory of briquettes.